An Analysis of the Interpretation of Surah Al-Qāri‘ah from the Perspectives of Tafsir al-Ṭabarī and Tafsir al-Azhar - Zulyadein Zulyadein; Febri Wardani; Efizal Anwar (The Future of Education Journal, 2026)
This study was motivated by the widespread assumptions claiming that the Day of Judgment will occur on a specific date or time, despite the Qur'anic teaching that only Allah knows when it will take place. Accordingly, this study examines the interpretation of Surah Al-Qāri‘ah through the perspectives of Al-Ṭabarī and Buya Hamka to provide a more accurate understanding of the Qur'anic message regarding the Day of Judgment. This research employed a library research approach using the comparative exegesis (tafsīr muqāran) method. The primary data sources were Tafsir al-Ṭabarī and Tafsir al-Azhar, supported by relevant secondary references. The findings indicate that neither exegete specifies the exact time of the Day of Judgment, as its occurrence remains known only to Allah. Instead, both interpretations emphasize the conditions and events preceding and following the Day of Judgment. The analysis also reveals that Surah Al-Qāri‘ah possesses distinctive characteristics, particularly in its linguistic style. The repeated use of the term Al-Qāri‘ah strengthens the emphasis of the message, and the surah directly describes the condition of humanity and the Day of Judgment more explicitly than other related chapters, such as Surah Al-Zalzalah, which primarily focuses on the recompense of human deeds. Furthermore, the comparative analysis shows that both Al-Ṭabarī and Buya Hamka employ the tahlīlī method of Qur'anic exegesis, interpreting the Qur'an sequentially from Surah Al-Fātiḥah to Surah An-Nās. Both commentaries also share a linguistic (lughawī) orientation; however, their approaches differ. Buya Hamka emphasizes the linguistic and cultural context of the Indonesian archipelago, whereas Al-Ṭabarī bases his interpretation primarily on transmitted narrations (riwāyah).